The Swiss Health Literacy Survey: development and psychometric properties of a multidimensional instrument to assess competencies for health. (6th March 2012) - Wang, Jen; Thombs, Brett D.; Schmid, Margareta R.
Abstract Background Growing recognition of the role of citizens and patients in health and health care has placed a spotlight on health literacy and patient education. Objective To identify specific competencies for health in definitions of health literacy and patient‐centred concepts and empirically test their dimensionality in the general population. Methods A thorough review of the literature on health literacy, self‐management, patient empowerment, patient education and shared decision making revealed considerable conceptual overlap as competencies for health and identified a corpus of 30 generic competencies for health. A questionnaire containing 127 items covering the 30 competencies was fielded as a telephone interview in German, French and Italian among 1255 respondents randomly selected from the resident population in Switzerland. Findings Analyses with the software MPlus to model items with mixed response categories showed that the items do not load onto a single factor. Multifactorial models with good fit could be erected for each of five dimensions defined a priori and their corresponding competencies: information and knowledge (four competencies, 17 items), general cognitive skills (four competencies, 17 items), social roles (two competencies, seven items), medical management (four competencies, 27 items) and healthy lifestyle (two competencies, six items). Multiple indicators and multiple causes models identified problematic differential item functioning for only six items belonging to two competencies. Conclusions The psychometric analyses of this instrument support broader conceptualization of health literacy not as a single competence but rather as a package of competencies for health.